Teaching writing: process, practice and policy - Keen, John (Changing English, 2022)
This article discusses two schemes for teaching writing in schools. One uses analysis of model texts into techniques and devices then application of these by students to their written compositions and one uses a process approach that includes pre-writing and exploring, drafting, sharing and discussing, revising and celebrating to exploit students' procedural knowledge of language at all levels of description. It argues that the process approach is more effective in facilitating the development of students' writing skills than the analysis-and-application methods currently adopted in secondary schools. It concludes that as the process approach is more effective, it will replace analysis-and-application for teaching writing.